TERAPAN KONSEP KESEHATAN JIWA IMAM AL-GHAZALI DALAM BIMBINGAN DAN KONSELING ISLAM - Aliah Purwakania Hasan (Universitas Sultan Ageng Tirtayasa, 2017)
Mental health is an ideal condition in which a person is not only physically, mentally, spiritually, and socially healthy, but also has the potential that can make people live productively. However, in reality various mental health problems arise in society. This study aims to discuss mental health based on the thoughts of Imam Al-Ghazali. This study is a literature study using content analysis techniques. Mental health is seen as a model consisting of the strength of aqidah, the liberation of the heart disease, the development of noble character, terbinanya adab good in social relations, and the achievement of happiness in the world and the hereafter. This paper discusses various methods to achieve mental health based on Imam al-Ghazali's thought, tailored to the need for guidance and counseling. The various benefits of applied mental health concepts in guidance and counseling are also described in this study Keywords: Islamic psychology, mental health, Islamic education